Targeting of Protein’s Messenger RNA for Viral Replication, Assembly and Release in SARS-CoV-2 Using Whole Genomic Data From South Africa: Therapeutic Potentials of Cannabis Sativa L - Erukainure, Ochuko L.; Matsabisa, Motlalepula G.; Muhammad, Aliyu; Abarshi, Musa M.; Amaku, James F.; Katsayal, Sanusi B.; Nde, Adeline Lum (Frontiers in Pharmacology, 2021)
The possible evolutionary trend of COVID-19 in South Africa was investigated by comparing the genome of SARS-CoV-2 isolated from a patient in KwaZulu-Natal, South Africa with those isolated from China, Spain, Italy, and USA, as well as the genomes of Bat SARS CoV, Middle East Respiratory Syndrome Coronavirus (MERS-CoV), Mouse Hepatitis Virus (MHV), and Infectious Bronchitis Virus (IBV). Phylogenetic analysis revealed a strong homology (96%) between the genomes of SARS-CoV-2 isolated from KwaZulu-Natal, South Africa and those isolated from the study countries as well as those isolated from bat SARS CoV, MERS-CoV, MHV and IBV. The ability of phytocannabinoids from Cannabis sativa infusion to interact with gene segments (mRNAs) coding for proteins implicated in viral replication, assembly and release were also investiagted using computational tools. Hot water infusion of C. sativa leaves was freeze-dried and subjected to Gas Chromatography-Mass Spectroscopy analysis which revealed the presence of tetrahydrocannabivarin, cannabispiran, cannabidiol tetrahydrocannabinol, cannabigerol, and cannabinol. Molecular docking analysis revealed strong binding affinities and interactions between the phytocannabinoids and codon mRNAs for ORF1ab, Surface glycoprotein, Envelope protein and Nucleocapsid phosphoprotein from SARS-CoV-2 whole genome which may be due to chemico-biological interactions as a result of nucleophilic/electrophilic attacks between viral nucleotides and cannabinoids. These results depict the spread of SARS-CoV-2 is intercontinental and might have evolved from other coronaviruses. The results also portray the phytocannabinoids of C. sativa infusion as potential therapies against COVID-19 as depicted by their ability to molecularly interact with codon mRNAs of proteins implicated in the replication, translation, assembly, and release of SARS-CoV-2. However, further studies are needed to verify these activities in pre-clinical and clinical studies